2018
DOI: 10.3390/brainsci8040058
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Use of New Psychoactive Substances by Individuals in Treatment for Substance Misuse in the UK

Abstract: Substance misuse services need to meet the growing demand and needs of individuals using new psychoactive substances (NPS). A review of the literature identified a paucity of research regarding NPS use by these individuals and UK guidelines outline the need for locally tailored strategies. The purpose of this qualitative study was to identify and explore key themes in relation to the use of NPS by individuals receiving community treatment for their substance use. Electronic records identified demographics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
(109 reference statements)
0
28
0
1
Order By: Relevance
“…With NPS' diffusion on the web, a rapid increase in the number of these drugs was observable as early as the beginning of the 2000s (Schifano et al, 2003). Popularity of NPS can mainly be attributed to their easy availability (e.g., online purchase), relatively low price, high purity, perceived safety profile or misbeliefs about their safety as well as their temporary legal status (e.g., Gittins et al, 2018). Furthermore, NPS became immensely popular in an era in which the availability and purity of classic drugs -such as cocaine or heroin -decreased (e.g., Zawilska, 2017), therefore users of formerly scheduled substances shifted to NPS consumption.…”
Section: Introductionmentioning
confidence: 99%
“…With NPS' diffusion on the web, a rapid increase in the number of these drugs was observable as early as the beginning of the 2000s (Schifano et al, 2003). Popularity of NPS can mainly be attributed to their easy availability (e.g., online purchase), relatively low price, high purity, perceived safety profile or misbeliefs about their safety as well as their temporary legal status (e.g., Gittins et al, 2018). Furthermore, NPS became immensely popular in an era in which the availability and purity of classic drugs -such as cocaine or heroin -decreased (e.g., Zawilska, 2017), therefore users of formerly scheduled substances shifted to NPS consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have addressed the inadequacy in essential knowledge and skills required by HCPs on NPS to inform various interventions and highlighted the need for education on these novel molecules [38][39][40][41][42][43]. However, several studies only focused on specific professions and geographical locations in the UK [40][41][42][43].…”
Section: Studies Exploring Nps Knowledge Among Healthcare Professionamentioning
confidence: 99%
“…Similarly, Owie et al [42] found that most psychiatrists had inadequate overall knowledge of NPS. Lastly, Gittins et al [39] utilised semi-structured interviews to gather detailed information from clients regarding their NPS use and concluded there is a need for further education and training for HCPs, who encounter NPS service users by adopting multi-agency and multi-disciplinary approaches to gauge awareness of changing trends in NPS use. When and where appropriate, referral to drug and alcohol treatment services or other professionals, such as psychiatry, sexual health or social services can be offered to individuals [47].…”
Section: Studies Exploring Nps Knowledge Among Healthcare Professionamentioning
confidence: 99%
“…Today evidence shows addiction to prescription drugs (e.g. painkillers and sedatives) is responsible for more deaths than heroin and cocaine; thus misuse of legal medication has become the latest drug scare in Northern Ireland boundaries between legal and illegal drugs are increasingly fluid as users, and addicts in particular, become 'polydrug users' (Duff, 2015;Gittins et al, 2018). It is very common to find problematic drugs use related to a potentially lethal mixture of drugs obtained from illegal markets (e.g.…”
Section: Northern Ireland: Drugs Paramilitarism and Planningmentioning
confidence: 99%